A self-assembled dual-phase composite as a precursor of high-performance anodes for intermediate temperature solid oxide fuel cells. Issue 87 (16th October 2018) - Song, Yefeng; Yin, Yi-Mei; Li, Linsen; Chen, Zonghai; Ma, Zi-Feng
Abstract : A durable high-performance anode composed of Fe–Cu nano-fibers, a Ruddlesden–Popper layered perovskite and a single perovskite is prepared from a dual-phase precursor. Abstract : A durable high-performance anode with a unique microstructure of a hetero-structured surface layer and exsolved Fe–Cu bimetal nano-fibers is fabricated from a self-assembled dual-phase precursor consisting of a single perovskite (SP) and a Ruddlesden–Popper (RP) layered perovskite component. This work opens up new opportunities to fabricate high-performance anodes for IT-SOFCs.